Ijtihad dar fiqh-i Islām-i - Furqānī, ʻAbd al-Salīm (Da Iṭṭ ilāʻātū aw Kultūr Vizārat. Mu̓assassah-̓i Tab̄ʻi Tab̄ʻi Kutub-i Bayhaqī, 1977)
On the different aspects of ijtihād (theological decision ) under Islamic law.